The Effect of Problem-Based Learning (PBL) Model and Learning Motivation on Reading Comprehension Skills - Raudhatul Jannah; Elfia Sukma; Muhammadi Muhammadi; Ulfia Rahmi (Journal of Educational Sciences, 2026)
The urgency of this study is strengthened by preliminary findings at SDN 28 Padang Sarai, which showed that many students still struggled with reading fluency, text comprehension, and answering questions based on textual information. Therefore, active and student-centered learning models are needed to improve students’ reading comprehension skills. This study aims to examine the effect of the Problem-Based Learning (PBL) model and learning motivation on students’ reading comprehension skills. This study employed a quantitative approach with a 2×2 factorial experimental design involving fourth-grade students at SDN 28 Padang Sarai. Data were collected through reading comprehension tests and learning motivation questionnaires and analyzed using descriptive statistics and two-way ANOVA. The findings revealed that students taught using the PBL model achieved higher scores than those taught using conventional instruction. The results also showed that both the learning model and learning motivation had significant effects on reading comprehension skills. However, no significant interaction effect was found between the two variables. Therefore, PBL is recommended to improve reading instruction in elementary schools.